Water flow and sediment transport at open-channel confluences: an experimental study - Yuan, Saiyu; Tang, Hongwu; Xiao, Yang; Qiu, Xuehan; Xia, Yang (Journal of hydraulic research, 2018)
The knowledge of the dynamics of urban channel confluences is insufficient as most past studies have focused on natural river confluences. This paper reports experimental observations on bed morphology and hydrodynamics of the urban confluences and their dependence to the discharge ratio. Typical hydrodynamic and morphological features such as the shear layer, helical cells, bars and scour holes are identified. Nevertheless, the presence of a region of low-velocity flow for a small discharge ratio differs from results obtained in previous studies. Two sand ridges associated with the corridors of the eroded sediment from the scour holes merge into a mid-stream bar. Results also show that the intense shear towards the bed by downwelling and upwelling flows involved in helical motions is responsible for the mid-stream scour hole.